Faultlines : (Bulwark book, 1999)
Faultlines is the first series of its kind in South Asia, bringing an inter-disciplinary focus to bear upon issues of internal security and conflict management, and on related areas of public policy. It serves as an outstanding source, both of primary data as well as of research papers, on issues of strife and internal security.